1980
DOI: 10.1002/jmv.1890060305
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey to detect subclinicai junían virus infection in laboratory personnel

Abstract: Serological survey for detecting subclinical infections with Junín virus, the etiological agent of Argentine hemorrhage fever, was carried out in a group of 107 individuals working in laboratories where this virus was handled. The group was divided into high risk and low risk personnel according to the degree of exposure to the virus. Neutralizing tests were performed in Vero cell cultures to detect circulating antibodies. Results were evaluated comparatively with those obtained in a previous survey. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Previous studies had shown that Junin virus produces inapparent infection in human beings, both among rural workers of the endemic area and also among laboratory personnel working with Junin virus [Weissenbacher et al, 1976;Weissenbacher et al, 1978;Weissenbacher et al, 1980;Guerrero et al, 19821. The results of the present study demonstrate that the prevalence of inapparent infection is lower than that of clinical infection, in contrast to many other viral diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had shown that Junin virus produces inapparent infection in human beings, both among rural workers of the endemic area and also among laboratory personnel working with Junin virus [Weissenbacher et al, 1976;Weissenbacher et al, 1978;Weissenbacher et al, 1980;Guerrero et al, 19821. The results of the present study demonstrate that the prevalence of inapparent infection is lower than that of clinical infection, in contrast to many other viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The serum samples were taken during the same time period under comparable conditions. The neutralization test was sensitive enough to determine the antibodies in all individuals who had suffered from the disease between 2 and 14 years previously, confirming the long-term persistence of neutralizing antibodies [Weissenbacher et al, 19761. Previous studies had shown that Junin virus produces inapparent infection in human beings, both among rural workers of the endemic area and also among laboratory personnel working with Junin virus [Weissenbacher et al, 1976;Weissenbacher et al, 1978;Weissenbacher et al, 1980;Guerrero et al, 19821. The results of the present study demonstrate that the prevalence of inapparent infection is lower than that of clinical infection, in contrast to many other viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Вирусемия чаще регистрировалась в острый период заболевания, а примерно через 20 дней после инфицирования -в единичных случаях [16]. Ненарушенная репродуктивная способность хозяев и эффективность постнатального переноса вируса Хунин указывают на вероятный вклад вертикальной передачи в поддержание вируса во времени [74]. G.Carballal и соавт.…”
unclassified